Atuação do cirurgião dentista no programa saúde na escola em municípios do Paraná - Schio, Gione André (2018)
The health actions that take place in the school environment are fundamental to share knowledge, to exercise the intersectoriality and to increase the access of the school community to health services, since the last two epidemiological surveys carried out in Brazil, in 2003 and 2010, respectively, demonstrated that the children oral health conditions demand attention. In addition, the National Survey of School Health (PeNSE) revealed a worsening in the students' general profile from 2009 to 2015, with a reduction in the proportion of brushing and an increase in the percentage of reported toothaches. To develop health actions in the school environment, the Federal Government instituted the Health in School Program (PSE) in 2007. It is a partnership between the Ministries of Health and Education, which aims to increase the access of the school community to health services and to contribute to the integral formation of the students through actions of promotion and prevention in regard to health care. The program has several lines of action, including oral health. The present study aimed to analyze the knowledge and performance of dental surgeons in the Health in School Program (PSE) in the municipalities that constitute the 8th Regional Health Center of Paraná. On this account, an exploratory study of quantitative-qualitative approach was carried out. A questionnaire with closed and open questions was sent to the professionals through an online platform, addressing issues related to the operation of the program, the actions planned for dental surgeons and their evaluation of the Program. The quantitative data were systematized and distributed in a table, and the qualitative data submitted to content analysis in the thematic analysis modality. A total of 38 dental surgeons working in the PSE completed the questionnaire. The activities that are most frequently developed focus on Component I (clinical evaluation) for the diagnosis and treatment of oral diseases. On Component II (health promotion and prevention), health prevention and education activities stand out. However, the lack of interest of the parents, the omission of the school, the scarcity of resources and the difficulty of multiprofessional work were cited as obstacles to perform them. It has been identified that dental surgeons are distanced from collective actions that happen through the PSE because they do not take part in moments of collective agreement. The results show that intersectoral practices are not part of the professional routine and are considered challenges to be faced. Difficulties were found regarding the training of professionals, since they were not prepared to act in the Program and did not participate in permanent education actions related to the theme. Therefore, it is paramount to expand promotion and prevention actions, in order for all municipalities to act beyond curative actions.